Possible Integrative Actions of Leptin and Insulin Signaling in the Hypothalamus Targeting Energy Homeostasis - Thon, Mina; Hosoi, Toru; Ozawa, Koichiro (Frontiers in Endocrinology, 2016)
Obesity has emerged as one of the most burdensome conditions in modern society. In this context, understanding the mechanisms controlling food intake is critical. At present, the adipocyte-derived hormone leptin and the pancreatic β-cell derived hormone insulin are considered the principal anorexigenic hormones. Although leptin and insulin signal transduction pathways are distinct, their regulation of body weight maintenance is concerted. Resistance to the central actions of leptin or insulin is linked to the emergence of obesity and diabetes mellitus. A growing body of evidence suggests a convergence of leptin and insulin intracellular signaling at the insulin–receptor–substrate–phosphatidylinositol-3-kinase (IRS-PI3K) level. Moreover, numerous factors mediating the pathophysiology of leptin resistance, a hallmark of obesity, such as endoplasmic reticulum (ER) stress, protein tyrosine phosphatase 1B (PTP1B) and suppressor of cytokine signaling 3 (SOCS3) also contribute to insulin resistance. Recent studies have also indicated that insulin potentiates leptin-induced signaling. Thus, a greater understanding of the overlapping functions of leptin and insulin in the central nervous system (CNS) is vital to understand the associated physiological and pathophysiological states. This mini-review focuses on the crosstalk and integrative signaling of leptin and insulin in the regulation of energy homeostasis in the brain.